2017
DOI: 10.18320/jimd/201704.0127
|View full text |Cite
|
Sign up to set email alerts
|

5. Gender based dimorphism in host response to viral infection: Two interesting epidemiological trends observed during Chikungunya outbreak in Kerala

Abstract: Abstract:Introduction: Males and females respond differently to infection, which again is modified by the 'stage of life cycle' they belong to. This knowledge however is often neglected during surveys/ studies or while deliberating protocols for disease control. Materials and methods: Data collected without segregation of sexes in separate age groups may thus be biased, confounding conclusions and disease control strategies formulated based on them. We analyzed results of IgM ELISA tests for chikungunya virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…Nevertheless, the epidemiological hypothesis here fails to explain the gender gap in prevalence estimates provided by the participants. Indeed, these results are contrary to findings in India or Brazil, 54,55 since women did not show higher rates of CHIKV or ZIKAV infection than men. Therefore, the epidemiological explanation is unable to account sufficiently for these sociocultural differences regarding the accuracy of the perceived disease prevalence.…”
Section: Discussioncontrasting
confidence: 94%
“…Nevertheless, the epidemiological hypothesis here fails to explain the gender gap in prevalence estimates provided by the participants. Indeed, these results are contrary to findings in India or Brazil, 54,55 since women did not show higher rates of CHIKV or ZIKAV infection than men. Therefore, the epidemiological explanation is unable to account sufficiently for these sociocultural differences regarding the accuracy of the perceived disease prevalence.…”
Section: Discussioncontrasting
confidence: 94%
“…Furthermore, when comparing RNA concentrations between the unvaccinated and vaccinated groups significant reductions were attributed solely to female animals. Several epidemiological studies have indicated gender disparities in response to CHIKV infection that are likely attributable to differential immunological responses [ 25 , 26 , 27 ]. Gender differences in the immunological response were not evaluated given group size limitations, but the consistent differences in gender response here combined with epidemiological reports support continued assessment of gender and age differences following CHIKV infection.…”
Section: Discussionmentioning
confidence: 99%